Potensi Risiko Kesehatan Akibat Pajanan Mikroplastik dari Lingkungan Pesisir dan Biota Laut - Risma Ayustri Ariesusanto (Jurnal Ilmiah Kedokteran dan Kesehatan, 2026)
Microplastics are plastic particles smaller than 5 mm formed through the degradation of plastic waste in the environment. Coastal areas are major accumulation zones for microplastics due to household, fisheries, and industrial activities, along with inadequate waste management. This article aims to review the potential health risks associated with microplastic exposure from coastal environments and marine biota. A descriptive-narrative literature review was conducted using articles obtained from Google Scholar, PubMed, ScienceDirect, and the Directory of Open Access Journals. The selected literature consisted of publications from 2020 to 2025 discussing microplastics in coastal environments, marine organisms, exposure pathways, and potential effects on human health. The review found that microplastics have been detected in seawater, coastal sediments, fish, and shellfish consumed by humans. Human exposure may occur through seafood consumption, drinking water, and inhalation. Several studies have also identified microplastics in human stool, blood, placenta, lung tissue, kidney tissue, and urine. Microplastics may induce inflammation, oxidative stress, metabolic disruption, cellular damage, and act as carriers of organic pollutants and heavy metals. However, epidemiological evidence regarding their health effects in humans remains limited. Further studies using standardized methods and stronger plastic pollution control are needed to reduce human exposure to microplastics.